MIĘDZY EKSPERYMENTEM A DOŚWIADCZENIEM POKOLENIOWYM." PAMIĘTAM" PIOTRA STANKIEWICZA JAKO LITERACKI EKWIWALENT KOLEKCJI - Barańska, Aleksandra; Lachman, Magdalena (Prace Polonistyczne, 2024)
The article offers an interpretation of Piotr Stankiewicz’s 2021 Pamiętam (I Remember). Barańska and Lachman make an extensive use of existing interviews given by the author as well as critical opinions and reviews. The analysis centres on two aspects of the book. First of all, the authors examine intertextual references. Stankiewicz uses a concept that was earlier introduced by Joe Brainard in I Remember (1970, revised 1975) and Georges Perec in Je me souviens (1978) and elaborated by other writers, and he adapts it to the Polish context. Furthermore, Barańska and Lachman discuss the book in the context of experimental literature and search for an appropriate genre designation for it. Secondly, the authors examine to what extent and on which organizational levels the concept of a collection can be applied to Pamiętam. From this perspective, they analyze the construction and composition of its message, the themes addressed by Stankiewicz, and his presentation techniques. Barańska and Lachman suggest that the overarching idea informing the text was created not so much because of the writer’s desire to depict the workings of memory, but rather out of his need to portray his own generation. In fact, Stankiewicz primarily addresses the book to his peers, with whom he shares similar experiences of participating in culture and in specific historical, political, and social processes.